Measuring Factors Determining Private Label Purchase - S, Jayakrishnan; Chikhalkar , Rekha D; Chaudhuri, Ranjan (Asian Journal of Empirical Research, 2016)
Indian retail sector has become competitive with the emergence of organized retail players. Currently retailers are focusing on developing their own brands or private labels to enhance customer loyalty, to add diversity and for better margins. The study primarily looks into understanding the consumer preference for private labels or store brands in breakfast cereals, snacks category (biscuits and traditional snacks) and to measure the factors that determine the store brand purchase in these categories. Consumer responses are collected from the city of Mysore (India) using structured questionnaire. Five point Likert scale is used to measure the factors that determine private label purchase. Confirmatory factor analysis (CFA) is done for developing a measurement model for factors that determine private label purchase in breakfast cereals and snacks category. Private label brand price (PLB) and perceived quality have significant relationship between them. Price consciousness, private label brand price is found to have considerable influence on value consciousness. Product familiarity has substantial impact on value consciousness and perceived quality. Store image is shaped in consumer minds on the basis of private label brand price, price consciousness and perceived quality of private labels.